Consumer engagement dynamics: The role of social media marketing in building brand awareness and purchase intention among UMKM Bachiro - Nur Fadilah Surabi; Nurul Hidayah; Julyia Fani; Kalam Mahardika; Yuliana Yuliana; Rahmawati Rahmawati (Privietlab, 2025)
This study aims to analyze the extent to which social media marketing strategies influence brand awareness and consumers’ desire to purchase products from Bachiro MSMEs, with consumer involvement as a mediating variable. The approach used is quantitative, analyzing data using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method through SmartPLS 4 software. There were 110 respondents, all of whom were active social media users who had interacted (liked, commented, shared, etc.) with Bachiro SME content.The results of the analysis prove that social media marketing activities have a positive and significant impact on consumer engagement, brand awareness, and purchase intention. Consumer engagement has a significant effect on brand awareness and purchase intention and functions as a bridge that strengthens the relationship between social media marketing and these two aspects.